The variety “Saratovskaya zolotistaya” is 25 - S. N. Gaponov; V. M. Popova; G. I. Shutareva; N. М. Tsetva; T. M. Parshikova; S. A. Shchukin (Зерновое хозяйство России, 2018)
For 25 years due to its unique properties the spring durum wheat variety “Saratovskaya zolotistaya” (1993) is popular not only among grain and pasta producers, but also among breeders of Russia and the CIS countries. Due to its high combining ability, the variety has been introduced in all breeding programs of research institutions engaged in the breeding and cultivation of spring durum wheat as a source of high content of carotenoid pigments.